2019
DOI: 10.1097/mpa.0000000000001254
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Mortality Rates of Second Pancreatic Cancer Among Survivors of Digestive Cancers

Abstract: Objectives We analyzed the incidence and mortality rates of second pancreatic ductal adenocarcinoma (PDAC) among survivors of digestive cancers in South Korea. Methods We evaluated data from the Korea National Health Insurance to identify individuals with digestive cancers in 2005 to 2015. The standardized incidence ratios (SIRs) of second PDACs and survival rates were evaluated. Results Among 772,534 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…In particular, first primary bile duct and gallbladder cancers were shown to carry increased risks of developing second primary EPC in both sexes (SIR [2.2−5.0]). This finding was consistent with previous reports in the Western population (SIR [2.4−13.1]), and in the Korean population using a different nationwide database (SIR [4.4−156.8]) [7,9,10,24]. In addition to shared anatomy and physiology, there may be genetic traits, lifestyle or environmental factors, and medical conditions that may have had impacts on the development of second primary EPCs as shared determinants among bile duct, gallbladder, and pancreatic cancers [24,26].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In particular, first primary bile duct and gallbladder cancers were shown to carry increased risks of developing second primary EPC in both sexes (SIR [2.2−5.0]). This finding was consistent with previous reports in the Western population (SIR [2.4−13.1]), and in the Korean population using a different nationwide database (SIR [4.4−156.8]) [7,9,10,24]. In addition to shared anatomy and physiology, there may be genetic traits, lifestyle or environmental factors, and medical conditions that may have had impacts on the development of second primary EPCs as shared determinants among bile duct, gallbladder, and pancreatic cancers [24,26].…”
Section: Discussionsupporting
confidence: 93%
“…Decreased risk of second primary EPC after rectal cancer in this study (SIR [0.5−0.8]) reconfirmed the results from the literature (SIR [0.6−0.7]) [8,9,24]. However, the findings on decreased risks of second primary EPC after stomach or colon cancer in this study were contrary to those of other studies in North America, Europe [8,9,24], and Korea [7,11]. Although clarifying etiology was beyond the scope of this study, a few possible interpretations can be proposed.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…A pooled analysis study of international multicenter cancer registries reported that spPDAC accounted for 6.9% of all PDAC diagnoses ( 15 ). A Korean study showed that the type of FPC can affect the probability and prognosis of spPDAC ( 16 ). In a cohort study based on 273,144 samples, an increased incidence of pancreatic cancer was found in a population of patients with previous colon cancer ( 17 ).…”
Section: Introductionmentioning
confidence: 99%